Integration of Trivia Game Within the Metaverse Mall for Public Services in the City of Semarang - Widianto, Daniel Prasetya; Sanjaya, Ridwan; Pamudji, Andre Kurniawan (Soegijapranata Catholic University, 2024)
The lack of education regarding the metaverse mall application for public services has left the public confused when engaging in public service activities within it. To address this issue, a trivia game titled